2015
DOI: 10.1002/ange.201503345
|View full text |Cite
|
Sign up to set email alerts
|

Basicity Limits of Neutral Organic Superbases

Abstract: The potential limits of superbasicity achievable with different families of neutral bases by expanding the molecular framework are explored using DFT computations.Anumber of different core structures of non-ionic organosuperbases are considered (such as phosphazenes,g uanidinophosphazenes, guanidino phosphorus ylides). As imple model for describing the dependence of basicity on the extent of the molecular framework is proposed, validated, and used for quantitatively predicting the ultimate basicities of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…[4] In this context, Leito et al have just published ap aper elucidating the basicity limit of nonchelating neutral superbases by means of theoretical calculations. [5] They come to the conclusion that P-ylidic carbon bases should outperform classical phosphazene bases.T his statement is in accord with Koppel et al who demonstrated by theory that the intrinsic basicity of P-ylides distinctly exceeds that of phosphazenes:F or example,t he proton affinity of (Me 2 N) 3 P = CH 2 (274.5 kcal mol À1 )e xceeds that of the corresponding phosphazene (Me 2 N) 3 P=NH (256.3 kcal mol À1 )b yabout 18 kcal mol À1 . [6] Going back to early works by Alder,another approach to obtain extraordinarily basic compounds is accomplished in socalled proton sponges which exhibit two basic entities in close proximity.…”
mentioning
confidence: 99%
“…[4] In this context, Leito et al have just published ap aper elucidating the basicity limit of nonchelating neutral superbases by means of theoretical calculations. [5] They come to the conclusion that P-ylidic carbon bases should outperform classical phosphazene bases.T his statement is in accord with Koppel et al who demonstrated by theory that the intrinsic basicity of P-ylides distinctly exceeds that of phosphazenes:F or example,t he proton affinity of (Me 2 N) 3 P = CH 2 (274.5 kcal mol À1 )e xceeds that of the corresponding phosphazene (Me 2 N) 3 P=NH (256.3 kcal mol À1 )b yabout 18 kcal mol À1 . [6] Going back to early works by Alder,another approach to obtain extraordinarily basic compounds is accomplished in socalled proton sponges which exhibit two basic entities in close proximity.…”
mentioning
confidence: 99%
“…[4] In diesem Zusammenhang verçffentlichten Leito et al kürzlich eine Arbeit, die sich auf Basis theoretischer Berechnungen mit dem Basizitätslimit nicht-chelatisierender Superbasen beschäftigt. [5] Daraus geht hervor,d ass P-ylidische Kohlenstoffbasen eine hçhere Basizitäta ls die entsprechenden Phosphazene aufweisen. Diese Aussage stimmt mit einer Publikation von Koppel et al überein, die auf theoretischer Basis ebenfalls eine hçhere intrinsische Basizitätv on Phosphoryliden gegenüber Phosphazenbasen beschreiben.…”
unclassified
“…47 Even though they are more basic than common trialkylamines, the pKa values of their conjugate acids would not warrant them to qualify as superbasic substances. [48][49][50] Nevertheless, their associated anions possess sufficiently high nucleophilicity to attach weakly electrophilic CO2, enabling them to be used in CO2 gas capture and catalysis. 47,[51][52][53][54][55] In this paper, we refer to them as azolate ionic liquids (or salts).…”
Section: Introductionmentioning
confidence: 99%